#### Answer

$(x^{2}+2)(x^{2}+6)$

#### Work Step by Step

$x^{4}+8x^{2}+12=$
$x^{4}+2x^{2}+6x^{2}+12=$
$x^{2}(x^{2}+2)+6(x^{2}+2)=$
$(x^{2}+2)(x^{2}+6)$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$(x^{2}+2)(x^{2}+6)$

$x^{4}+8x^{2}+12=$
$x^{4}+2x^{2}+6x^{2}+12=$
$x^{2}(x^{2}+2)+6(x^{2}+2)=$
$(x^{2}+2)(x^{2}+6)$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.